INTEGRATION OF TRADITIONAL AND CONTEMPORARY TECHNIQUES IN FINE ARTS - Orinov Muhammadjon Khojakbar ogli (Modern American Journals, 2025)
This article examines the integration of traditional and contemporary techniques in fine arts, analyzing how this synthesis enriches the creative process and contributes to the evolution of visual culture. The article explores the conceptual and aesthetic significance of combining classical art forms with modern digital and technological tools. It highlights how contemporary artists draw on traditional craftsmanship while embracing innovations such as digital painting, 3D modeling, and mixed-media practices. The study further considers the role of this integration in art education and its impact on the development of hybrid artistic identities in today’s globalized art world.
Keywords: Fine arts, traditional techniques, contemporary techniques, digital art, mixed media, hybrid art, craftsmanship, visual culture, art education.